2009
DOI: 10.1002/cne.22158
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic retinal ON bipolar cell synapses in the OFF inner plexiform layer: Contacts with dopaminergic amacrine cells and melanopsin ganglion cells

Abstract: A key principle of retinal organization is that distinct ON and OFF channels are relayed by separate populations of bipolar cells to different sublaminae of the inner plexiform layer (IPL). ON bipolar cell axons have been thought to synapse exclusively in the inner IPL (the ON sublamina) onto dendrites of ON-type amacrine and ganglion cells. However, M1 melanopsinexpressing ganglion cells and dopaminergic amacrine (DA) cells apparently violate this dogma. Both are driven by ON bipolar cells, but their dendrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
187
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 156 publications
(205 citation statements)
references
References 76 publications
18
187
0
Order By: Relevance
“…Previous studies indicated that the functional IPL stratification schemes require amendment to include an accessory ON layer at the most distal portion of IPL stratum one, and perhaps throughout the entire OFF IPL (Dumitrescu et al, 2009;Hoshi et al, 2009). Our data are consistent with mixed ON-OFF processing throughout levels 0-45% of the IPL, consistent with bipolar cell stratification patterns in non-mammalians.…”
Section: On Cone Bipolar Cell Axonal Ribbons Throughout the Off Ipl Fsupporting
confidence: 87%
See 4 more Smart Citations
“…Previous studies indicated that the functional IPL stratification schemes require amendment to include an accessory ON layer at the most distal portion of IPL stratum one, and perhaps throughout the entire OFF IPL (Dumitrescu et al, 2009;Hoshi et al, 2009). Our data are consistent with mixed ON-OFF processing throughout levels 0-45% of the IPL, consistent with bipolar cell stratification patterns in non-mammalians.…”
Section: On Cone Bipolar Cell Axonal Ribbons Throughout the Off Ipl Fsupporting
confidence: 87%
“…G-H). All of the above are consistent with M1-type ipRGCs (Dumitrescu et al, 2009;Graham et al, 2008;Hoshi et al, 2009). Henceforth, we shall simply refer to it as ipRGC 12208.…”
Section: Rod Bipolar Cell Axonal Ribbons Do Not Provide Accessory On supporting
confidence: 60%
See 3 more Smart Citations